Pendekatan Hermeneutika Filosofis Dan Kritis Dalam Studi Islam Kontemporer - Sri Mulyani (CV. ITTC INDONESIA, 2025)
This article examines the philosophical and critical hermeneutical approaches as methodological foundations in contemporary Qur’anic interpretation. Philosophical hermeneutics rooted in the thoughts of Gadamer and Ricoeur emphasizes the dialogical, historical, and linguistic dimensions of understanding, where meaning emerges from the fusion of horizons between text and interpreter. Meanwhile, critical hermeneutics, represented by scholars such as Arkoun and Abu Zayd, highlights the need to uncover ideological structures, power relations, and dogmatic closures that shape traditional interpretations. By integrating these two perspectives, this study demonstrates how contemporary Qur’anic exegesis can become more contextual, emancipatory, and responsive to modern issues such as gender justice, ecological ethics, and human rights. This integrated framework provides a dynamic interpretative paradigm that bridges the continuity of revelation with the demands of current human realities.